Vanishing Point: an art/science collaboration and exhibition on the impact of microplastics in our oceans - Auman, HJ; Walsh, PH; Virtue, P; Olivier, F; Carnell, S; Cooper, K; Masters, D; Mausz, G; Muir Wilson, T (Makers' Space, Burnie, 2019)
THE PROJECT. Vanishing Point is an arts/science collaboration to raise awareness about the issues surrounding plastics pollution in the oceans and its ecological, biological and social impact. Initially the brainchild of wildlife artist Katherine Cooper, in 2015 Vanishing Points first exhibition was held at the Institute for Marine and Antarctic Studies. Katherine was joined by four other artists (Peter Walsh, Ron Moss, Toby Muir-Wilson and Sophie Carnell) and three scientists (Heidi Auman, Patti Virtue and Frederique Olivier) from the Institute for Marine and Antarctic Studies (IMAS, in Hobart, Tasmania) researching impacts of ocean plastics. The goal of the project was to raise awareness in the community about the impact of our daily use of plastics through art and science communication in a complementary and engaging manner. The 2017 exhibition included the work of two new artists, Di Masters Multi Media Artist and - and Gerhard Mausz - sculptor and designer. The exhibition expanded on the 2015 project by embracing the theme of Unseen. From micro-beads in personal care products, microfibres in synthetic clothing, and fragments derived from the breakdown of larger debris, micro-plastics are increasingly invading our marine systems and food chains. This is now recognised as a serious global environmental issue. THE SCIENCE. "As many as 51 trillion microplastic particles - 500 times more than stars in our galaxy - litter our seas, seriously threatening marine life." - United Nations report An estimated 5-13 million metric tons of plastic end up in our oceans each year. Microplastic debris begins the journey to the sea as consumer and industrial products like exfoliants, cosmetics and industrial abrasives, or breakdown of larger plastic items. Even synthetic fibres shed from our clothes during washing contribute to this unseen but now widespread marine pollution. Microplastics can affect wildlife in many harmful ways. Ingestion and physical obstruction can reduce feeding by marine life and lead to starvation. Microplastics act like sponges to chemical pollutants, and when eaten can affect growth, endocrine function and reproductive success. These contaminants also bioaccumulate through the food web. Plastic pollution on our beaches is obvious; however, microplastics in our oceans are often invisible. The aim of our exhibition is to help visualise this insidious problem. By raising awareness of the threats of microplastics, we can work together to find solutions to this unseen marine pollution. THE ART. Through the mediums of painting (Katherine Cooper), photography (Peter Walsh), sculpture (Gerhard Mausz), woodwork (Toby Muir Wilson), printmaking/drawing (Di Masters) and jewellery (Sophie Carnell), each of the artists involved bring their own particular viewpoint to the project. All of the artists live and work in Tasmania and have established merit in their chosen fields of practice. The works emerge from an inquiry-based pursuit that is common to both art and science, presenting a commentary on the multifaceted nature of both scientific research and artistic expression. Its possible to engage viewers through visual beauty and simplicity, leading them through a deeper story to raise awareness of the issue at hand - the dangers of plastic in our marine environment. We can all make a difference if we are mindful, and small changes to our behaviours can have a positive impact. Our oceans ARE worth protecting. THE COLLABORATION. Science communication to the general public is never easy. The general public can easily be overwhelmed or quickly lose interest in the complexities of scientific research. Conversely, the scientist often feels the science is too easily distorted or trivialised when attempts are summarised into a 1 minute news bite or 5 minute segment. Art provides a mechanism to engage the general public. Almost always, the goal of the artist is to hook the viewers interest with something visually stimulating, then lead them into a deeper experience. Most art is multi-layered and attempts to draw the viewer into the artists experience step by step. The viewers initial interest is drawn to a simple, visually pleasing object (like a bower bird is drawn to brightly coloured objects). The skill of the artist is then to hold the viewer's attention, unravelling a story, piece by piece, as their senses move around and through the artists work. By combining this skill of the artist with the knowledge of the scientist, its possible to engage viewers through visual beauty and simplicity, then lead them through a deeper story to raise awareness of the issue at hand.